ALIRAN-ALIRAN DALAM EKONOMI ISLAM - Maryam Batubara; Astri Sri Rezeki Harahap; Awaluddin Rambe; Imam Aldino; Khairani Ritonga (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2023)
In economics, both Islamic and conventional (general) economics, there are several different ideas. As we know, conventional (general) ideas or schools of thought about economics, be it classical, neoclassical, historical and other economic schools. In Islamic economics there are also economic schools which we often know as economic schools of thought. This type of research uses the library study method (library research) using several book references and previous research as references to strengthen this research. Data analysis in this research uses qualitative data analysis which aims to systematically search and compile data obtained from various existing sources. The existence of this economic school or school of thought has no other purpose than to evaluate or assess previous economic schools which were considered unable to solve economic problems, so that contemporary economic thinkers emerged which can be categorized into three groups of schools, namely the iqttishaduna school, the mainstream school and the critical alternative.